Khazanah Leksikon Perayaan Asyura Kota Serang - Devi, Ade Anggraini Kartika; Solihat, Ilmi (Universitas Lampung, 2024)
Ashura celebrations not only reflect spiritual aspects, but also represent the cultural entity of society as a whole. Ashura celebrations involve local religious and cultural values that interact and adapt to each other. This research aims to determine the lexicon of names and cultural meanings of Ashura celebrations in Serang City, Banten Province. The research technique used is descriptive qualitative with ethnographic interview methods, participant observation, and literature review which also includes an examination of the Kitab Kuning. The source of research data comes from the Ashura celebration in Serang City. Research findings show 18 Ashura celebration lexicon data that can be classified into three Ashura celebration times: 9 Muharram, 10 Muharram, and 11 Muharram. The Ashura celebration lexicon is grouped into (1) monomorphemic word-form lexicon, (2) polymorphemic word-form lexicon, and (3) phrase-form lexicon. Each lexicon has noun and verb categories.Keywords: lexicon, Ashura, ritual, religious